Capacity Building for Researchers, Academics, and Extension Experts to Support Climate-Smart Practice Implementation - Getachew, Tesfaye; Belay, Berhanu; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
In 2024, ICARDA, in collaboration with AICCRA and various partners, conducted a series of training sessions to enhance capacity in data management, genetic improvement and climate-smart livestock practices. A total of 56 participants attended these sessions, representing 17 Ethiopian universities, five research centers, regional and federal agricultural institutions, and international partners. The first training, held from July 4–6, 2024, at ILRI in Addis Ababa, focused on data management and analysis. A total of 24 participants gained practical skills in using the DTREO genetic database, analyzing baseline data with R, and estimating genetic parameters with WOMBAT, equipping them to improve data-driven breeding practices. A subsequent training session in Gambela City on July 15–16, 2024, targeted regional and federal agricultural institutions, focusing on CBBP implementation. The 32 participants engaged in hands-on exercises to define breeding objectives, enhance data collection, and evaluate current CBBPs. Recommendations emphasized strengthening the ongoing efforts to establish a breeding program and initiate animal identification and data collection. The group also emphasized the importance of traits such as kid growth rate, milk yield, twinning rate, and survival, with a view to improving goat productivity and livelihoods. These trainings reflect ICARDA’s commitment to sustainable small ruminant improvement, climate resilience, and knowledge sharing through capacity building. They enable participants to implement and scale impactful breeding practices across diverse contexts.